Evaluasi Penerapan Good Manufacturing Practice dan Sanitation Standard Operating Procedure pada Rumah Pemotongan Hewan Unggas di Bogor - Siti Nurjanah; Winiati Puji Rahayu; Rara Nabila Najib (Jurnal Ilmu Pertanian Indonesia, 2021)
Microbial contamination in chicken meat is caused by unsanitary practices during slaughtering in poultry slaughtering house. Poultry slaughtering house need to apply Good Manufacturing Practice (GMP) and Sanitation Standard Operating Procedure (SSOP) system to produce the standard microbial requirements of meat. This study was aimed to evaluate the implementation of GMP and SSOP and categorize 30 slaughtering houses located in Bogor. Observation was carried out in 4 modern slaughtering houses (RPH-U) and 26 traditional slaughtering houses (TPH-U). Parameter evaluation was determined based on the Indonesian national standard SNI 01-6160-1999 and the veterinary control certificates which consisted of eight aspects of GMP and six aspects of SSOP. The categorization was clustered in five levels. The results showed that modern slaughtering houses were categorized into 1st and 2nd level, whilst traditional slaughtering houses were categorized into 2nd and 3rd level. The highest incompliance of GMP in modern slaughtering house was the waste treatment aspect (31%) and in traditional slaughtering house was the cold storage presence aspect (95%). The highest incompliance of SSOP in modern slaughtering house was the sanitation facilities and avoiding cross-contamination aspect (21%) and in traditional slaughtering house was the cleanliness of food contact surface aspect (97%). There are some recommendations for improvement the fulfillment of GMP and SSOP aspects based on the critical parameters. Keywords: chicken meat, Good Manufacturing Practice, modern slaughteringhouse, Sanitation Standard Operating Procedure, standard slaughteringhouses